The Privacy Paradox: Factors influencing information disclosure in the use of the Internet of Things (IoT) in South Africa - Davids, Natheer (Department of Information Systems, 2021)
The Internet of Things (IoT) has been acknowledged as one of the most innovative forms of technology since the computer, because of the influence it can have on multiple sectors of physical and virtual environments. The growth of IoT is expected to continue, by 2020 the number of connected devices is estimated to reach 50 billion. Recent developments in IoT provide an unprecedented opportunity for personalised services and other benefits. To exploit these potential benefits as best as possible, individuals are willing to provide their personal information despite potential privacy breaches. Therefore, this paper examines factors that influence the willingness to disclose personal information in the use of IoT in South Africa (SA) with the use of the privacy calculus as the theoretical underpinnings of this research. The privacy calculus accentuates that a risk-benefit trade off occurs when an individual decides to disclose their personal information, however, it is assumed that there are more factors than perceived risks and perceived benefits that influence information disclosure. After analysing previous literature, this study identified the following factors; information sensitivity, privacy concerns, social influence, perceived benefits, (perceived) privacy risks and privacy knowledge as possible key tenants in relation to willingness to disclose personal information. This research took on an objective ontological view, with the underlying epistemological stance being positivistic. The research incorporated a deductive approach, employing the use of a conceptual model which was constructed from a combination of studies orientated around privacy, the privacy calculus and the privacy paradox. Data for this research was collected using the quantitative research approach, through the use of an anonymous online questionnaire, where the targeted population was narrowed down to the general public residing within SA that make use of IoT devices and/or services. Data was collected using Qualtrics and analysed using SmartPLS 3. SmartPLS 3 was used to test for correlations between the factors which influence information disclosure in the use of IoT by utilising the complete bootstrapping method. A key finding was that the privacy paradox is apparent within SA, where individuals pursue enjoyment and predominantly use IoT for leisure purposes, while individuals are more likely to adopt self-withdrawal tendencies when faced with heightened privacy concerns or potential risks.